2022
DOI: 10.3390/pharmaceutics14061232
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Solubility and Antitumor Activity of Annona Squamosa Seed Oil via Nanoparticles Stabilized with TPGS: Preparation and In Vitro and In Vivo Evaluation

Abstract: Annona squamosa seed oil (ASSO), which is a waste product in the extraction of annonaceous acetogenins (ACGs), displays good antitumor activity against a variety of tumor cells. However, ASSO is insoluble and has low bioavailability. In order to improve the solubility and application value of ASSO, the seed oil nanoparticles (ASSO-NPs) were successfully prepared only using TPGS as a stabilizer. ASSO-NPs obtained were spherical with a uniform size (less than 200 nm). ASSO-NPs showed the good storage stability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We think the major reason that 90 mg/kg of OA-ENPs displayed much better tumor targetability than 30 mg/kg of OA-ENPs and 10 mg/kg of OA-ENPs was the result of dosing effect, which was later confirmed by Hui Ao et al. ( 2022 ).…”
Section: Resultsmentioning
confidence: 80%
“…We think the major reason that 90 mg/kg of OA-ENPs displayed much better tumor targetability than 30 mg/kg of OA-ENPs and 10 mg/kg of OA-ENPs was the result of dosing effect, which was later confirmed by Hui Ao et al. ( 2022 ).…”
Section: Resultsmentioning
confidence: 80%
“…Even within the same species, there may be variations in the FA composition of the seed oil. For instance, research revealed that oleic (37.0%), palmitic (25.1%), and linoleic (10.9%) acids were the predominant FAs in ASSO [74][75][76]. In contrast, 32.0% linoleic and 29.0% oleic contents have been observed [60].…”
Section: Proximate Composition Of Annona Seeds and Seed Oil Extractionmentioning
confidence: 99%